Human parvovirus B19 seropositivity in multiple sclerosis patients with arthralgia - Bulut, S.; Berilgen, M. S.; Akbulut, H.; Kansiz, F.; Kamanli, A.; Mungen, B. (Blackwell Publishing, 2004)
[Abstract Not Available]